Cutting surfaces and applications to periodic points and chaotic-like dynamics - Pireddu, Marina; Zanolin, Fabio (Topological Methods in Nonlinear Analysis, 2007)
In this paper we propose an elementary topologicalapproach which unifies and extends various different resultsconcerning fixed points and periodic points for maps defined onsets homeomorphic to rectangles embedded in euclideanspaces. We also investigate the associated discrete semidynamicalsystems in view of detecting the presence of chaotic-likedynamics.